A Conceptual Framework for Designing Pedestrian-Oriented Spaces for the Elderly to Facilitate Their Wayfinding in Urban Environments - Ali Moslehi; Mehrnoosh HasanZadeh (طراحی و برنامه ریزی در معماری و شهرسازی)
Elderly individuals, as a vulnerable age group in society, are at risk of isolation and loneliness and may become disconnected from urban environments. One of the exacerbating factors of this issue is the feeling of disorientation when faced with unfamiliar urban spaces. When elderly people are unable to engage in urban settings for various reasons, their inclination to be present in these environments gradually decreases, resulting in a choice of solitude and isolation. One of the factors that can help prevent this is the design of urban environments tailored to the needs of the elderly. Elderly individuals are more likely to feel comfortable in environments that are familiar to them, where they do not feel lonely or disoriented and can navigate on foot or via public transportation without obstructions and barriers. Therefore, the aim of this research is to identify the factors influencing elderly individuals’ wayfinding and orientation in urban environments, particularly in pedestrian spaces, to establish a framework for the design and navigation of elderly individuals in pedestrian-oriented environments. In this context, semi-structured interviews were conducted with a number of elderly residents of Tehran, randomly selected without considering their neighborhoods or areas of residence. Part of the interview consisted of multiple-choice questions, while another part included semi-structured and open-ended questions, from which important concepts were extracted using content analysis. Ultimately, factors that contribute to the design of pedestrian-oriented urban environments, considering appropriate wayfinding for the elderly, were identified, including readability, accessibility, continuity, safety, and education.